Plasticity of parental CENH3 incorporation into the centromeres in wheat × barley F1 hybrids - Mihók, Edit; Polgári, Dávid; Lenykó-Thegze, Andrea; Makai, Diána; Fábián, Attila; Ali, Mohammad; Kis, András; Sepsi, Adél; Sági, László (Frontiers in Plant Science, 2024)
Incorporating the centromere-specific histone H3 protein CENH3 into the centromeric DNA nucleosomes is indispensable for accurate centromere function and balanced chromosome segregation in most eukaryotes, including higher plants. In the cell nuclei of interspecific hybrids, divergent centromeric DNAs cohabit and lead the corresponding parental chromosomes through the mitotic and meiotic cell divisions. Depending on the transmission of the parental chromosomes carrying the CENH3-encoding genes, CENH3 proteins from one or both parents may be present in these hybrids. The incorporation of parental CENH3 proteins into the divergent centromeres and their role in the chromosome elimination process frequent in interspecific hybrids is still poorly understood. Here, we produced wheat × barley F1 hybrids that carried different combinations of barley chromosomes with genes encoding for either one (αCENH3) or both barley CENH3 protein variants (α-and βCENH3). We generated specific antibodies distinguishing between the two wheat CENH3 proteinvariants and barley αCENH3 and applied them together with FISH probes to detect the precise pattern of parental CENH3 deposition into the wheat and barley centromeric nucleosomeDNAs. Analysis of somatic and meiotic nuclei of the wheat × barley hybrids revealed the plasticity of the maternal (wheat) CENH3 proteins to become incorporated into the paternal (barley) centromeric nucleosomes to incorporate cross-species (wheat) CENH3. However, no evidence for maternal centromerepaternal CENH3 plasticity was detected in this study. The significance of the unilateral centromere plasticity and possible patterns of CENH3 incorporation into centromeres in interspecific hybrids are discussed.